Target and Non-Target Approaches for Food Authenticity and Traceability - Amaral, Joana S. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Over the last few years, the subject of food authenticity and food fraud has received increasing attention from consumers and other stakeholders, such as government agencies and policymakers, control labs, producers, industry, and the research community. Among the different approaches aiming to identify, tackle, and/or deter fraudulent practices in the agri-food sector, the development of new, fast, and accurate methodologies to evaluate food authenticity is of major importance. This book, entitled "Target and Non-Target Approaches for Food Authenticity and Traceability", gathers original research and review papers focusing on the development and application of both targeted and non-targeted methodologies applied to verify food authenticity and traceability. The contributions regard different foods, among which some are frequently considered as the most prone to adulteration, such as olive oil, honey, meat, and fish. This book is intended for readers aiming to enrich their knowledge through reading contemporary and multidisciplinary papers on the topic of food authentication.